¿Segregación o integración?: Relaciones entre las ciudades griegas helenísticas de Asia Menor y las poblaciones anatólicas - Lozano, Arminda (Gerión. Revista de Historia Antigua, 2002)
This article tries to offer a contribution, as far as the limited documentation allows it, to the study of the domestic policies of the various Seleucid sovereigns toward the Greek cities in the occidental part of their empire. The role played by these cities toward the preexisting population in these territories will be at the center point of this analysis, trying to discover what type of relationship was established between these two groups which had their particular way of living.